How to resolve cryptic species of polypores: an example in Fomes - Ursula Peintner; Regina Kuhnert-Finkernagel; Viana Wille; Franco Biasioli; Anton Shiryaev; Claudia Perini (IMA Fungus)
Abstract Species that cannot be easily distinguished based on morphology, but which form distinct phylogenetic lineages based on molecular markers, are often referred to as cryptic species. They have been proposed in a number of fungal genera, including the basidiomycete genus Fomes. The main aim of this work was to test new methods for species delimitation in cryptic lineages of polypores, and to define useful characters for species identification. A detailed examination of a number of different Fomes strains that had been collected and isolated from different habitats in Italy and Austria confirmed the presence of distinct lineages in the Fomes fomentarius clade. Our zero hypothesis was that the Mediterranean strains growing on Quercus represent a species which can be delimited based on morphological and physiological characters when they are evaluated in statistically relevant numbers. This hypothesis was tested based on phylogenetic analysis of the rDNA ITS region, morphological characters of basidiomes and pure cultures, growth rates and optimum growth temperature experiments, mycelial confrontation tests, enzyme activity tests and volatile organic compound (VOC) production. The Mediterranean lineage can unambiguously be delimited from F. fomentarius. A syntype of an obscure and previously synonymized name, Polyporus inzengae, represents the Mediterranean lineage that we recognize as Fomes inzengae, a distinct species. The rDNA ITS region is useful for delimitation of Fomes species. Moreover, also a variety of morphological characters including hymenophore pore size, basidiospore size, and diameter of skeletal hyphae are useful delimiting characters. The ecology is also very important, because the plant host appears to be a central factor driving speciation. Physiological characters turned also out to be species-specific, e.g. daily mycelial growth rates or the temperature range of pure cultures. The production of VOCs can be considered as a very promising tool for fast and reliable species delimitation in the future.